2018
DOI: 10.1038/s41598-018-30793-z
|View full text |Cite
|
Sign up to set email alerts
|

Facile and inexpensive fabrication of zinc oxide based bio-surfaces for C-reactive protein detection

Abstract: The paper reports a biosensor formed from antibody coated ZnO nano-crystals which has been prepared using a rapid and inexpensive fabrication method which utilises colloidal dispersion enhanced using sonication. This technique was used to prepare highly ordered and uniform nano-crystalline sensor surfaces on polyethylene terephthalate (PET) using 0.5%, 1% and 5% concentrations of zinc oxide nano-crystal suspensions. Impedance spectroscopy was employed to interrogate the sensor surfaces and confirmed high repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…The sensor response was plotted using readings taken at a frequency of 138 Hz. This frequency was selected as in previous work it demonstrated maximum changes in response to addition of a target analyte [15]. This observation concurred with Jacobs et al, who found that the electrical double layer is greater at frequencies below 1000 Hz and the most significant changes occurred around 100 Hz in their experiment to measure the protein troponin-T on a ZnO surface [16].…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The sensor response was plotted using readings taken at a frequency of 138 Hz. This frequency was selected as in previous work it demonstrated maximum changes in response to addition of a target analyte [15]. This observation concurred with Jacobs et al, who found that the electrical double layer is greater at frequencies below 1000 Hz and the most significant changes occurred around 100 Hz in their experiment to measure the protein troponin-T on a ZnO surface [16].…”
Section: Methodssupporting
confidence: 74%
“…200 μL of each suspension were dropped on to clean polyethylene terephthalate (PET) substrates (20 mm × 20 mm) separately to make ZnO/CuO nano-surfaces. Finally, they were dried in an oven at 65 C for 80 min and cooled down to room temperature, then stored in a dry atmosphere with silica gel for up to 2 days [15].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, Wang et al have concluded that ZnO NRs provided more protein interactions than other ZnO nanostructured materials 37 , reinforcing the development of ZnO NR-based immune-dependent platforms. For instance, Cao and colleagues have developed ZnO NRs-based sensors to immunodetect C-reactive protein, where a colloidal dispersion technique was used to cover PET 4,38 . Similarly, Tamashevski et al 15 developed a ZnO NRs-based sensor towards the immunodetection of human leukemic cells, where gaseous-dispersive synthesis was used to cover a glass substrate.…”
Section: Resultsmentioning
confidence: 99%
“…9.5, makes it suitable to adsorb negatively charged proteins, such as enzymes and antibodies, with lower IEPs 3 . As such, various types of biomolecules, including proteins 4 , enzymes 5 , antibodies 6 , as well as nucleic acids 7 , have been successfully bound to ZnO nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted using anti-FIX as bioreceptor, while FIX as the target for this detection and the detection limit was 100 pM. While the specific attention was narrowed down by implementing thin film technology to design novel nanosensors 6 . Thin film materials are unique due to their nano-or micro-dimensions nature followed by a superior electrical conductivity for quick and accurate outcome, which would easier for early detection system in the medical field 7 .…”
mentioning
confidence: 99%